Nasopharyngeal carcinoma (NPC) with liver metastasis in pregnancy - Zakaria, Atiqah Farah; Ishak, Azlan Iskandar; Han, Kong Min; Muhamad Yunus, Razif (Japan International Cultural Exchange Foundation, 2016)
Introduction: Cancer in pregnancies is the second most common cause of death after trauma in woman of reproductive age and confounds about 0.1 to 0.2% of pregnancies1,2) and rarely nasopharyngeal carcinoma being the aetiology. Objective: This report describes a pregnant woman in which an advanced-stage NPC was diagnosed and managed accordingly with a review of some related literature reviews. Case report: 29 year old Chinese lady was diagnosed with nasopharyngeal carcinoma (NPC) during her third trimester with very short history. She initially presented to us at 34 weeks of pregnancy with a painless right neck swelling and a chronic non-productive cough for one month duration. She was initially thought to have tuberculous lymphadenitis. A routine rigid endoscopic nasopharyngoscope examination revealed a right Fossa of Rosenmuller (FOR) mass. Biopsy of the nasal mass and fine needle aspiration cytology (FNAC) of the neck swelling further confirmed nasopharyngeal carcinoma- non keratinizing type. After discussion with her obstetrician and the patient, she underwent an elective induction of labor at 36 weeks of gestation, and delivered a healthy 2.77 kg baby boy. Computer tomography (CT) neck, thorax and abdomen were performed 2 weeks postpartum. The imaging showed fullness of the right FOR with metastases to right level 2 cervical lymph node along with metastatic deposits in 2 segments of the liver. She was then referred to oncology unit for further management. Conclusion: In conclusion, high index of suspicion is important in detection of NPC even in pregnant ladies with suspicious neck swelling. Method of detecting NPC early in pregnancy is essential in order to give optimize treatment, achieve potential for full recovery and also reduced the adverse risk and complications associated with NPC.